Panel And Spatial Panel Model Of Unemployment Rate For Selected Asian Countries - Lim, Bao Man (2024)
The unemployment rate has always been a concern in the global economic context. The main objective of this research is to examine the relationship between the economic freedom index (efi), index of governance quality, and economic indicators on the unemployment rate for selected asian countries. Therefore, this study explains and employs static panel data models, dynamic panel data models, and spatial panel data models to analyse the unemployment rate in the selected asian countries. The fixed effects model (fem) with robust panel and clustering is found to be the most suitable model for overall unemployment rate, male and female, which can address heteroskedasticity and serial correlation issues. Several of the economic freedom and governance quality indices were found to be significant in this study. Furthermore, spatial dependence is a condition where the outcome in one country depends on the outcome or other factors of another country. All test results indicate that the fem sdm for both effects (time and individual) for overall unemployment rate, male, and female is the most suitable model. The key factors that significantly affect the pattern of total and male unemployment rate of selected asian countries’ models, including government integrity, tax burden, monetary freedom, political stability no violence, and regulatory quality. While for the female unemployment rate, government integrity,